Immediate change in throughfall spatial distribution and canopy water balance after heavy thinning in a dense mature Japanese cypress plantation. Issue 2 (5th May 2015) - Nanko, Kazuki; Onda, Yuichi; Kato, Hiroaki; Gomi, Takashi
Abstract: This study revealed the influence of change in forest canopy structure by forest management practice for throughfall generation and canopy water interception process. Throughfall and stemflow were observed in a mature Japanese cypress ( Chamaecyparis obtusa ) plantation before and after thinning. Decreased stem density (from 2400 to 1300 trees ha −1 ) and basal area (from 107.6 to 60.4 m 2  ha −1 ) resulted in an increase in the throughfall fraction (from 58% to 79%) and decreases in the stemflow fraction (from 14% to 8.6%) and the canopy interception loss fraction (from 27% to 12%). Thinning also decreased spatial variability in throughfall and smoothed temporal persistence of throughfall among sampling points or rainfall events. These results were supported by the change in the throughfall balance between direct throughfall and released throughfall. The proportion of direct throughfall of incident rainfall changed from 0.16 to 0.42 owing to an increase in canopy gap. The distribution ratio of released throughfall from intercepted rainwater by canopy changed from 50% to 64% because of a decrease in foliage; this led to lower water storage in the canopy (from 1.83 to 0.82 mm), and thus less precipitation was needed to saturate the canopy. Consequently, the amount of throughfall increased and less precipitation was needed to stabilize the water flow path during the post‐thinning period. This study contributes to knowledge of differential canopy wetting processes and spatiotemporal heterogeneity of throughfall distribution in response to specific silvicultural prescription. Copyright © 2015 John Wiley & Sons, Ltd.